The effect of electrical corona on the rate of plant growth - 238482 Che Wan Nor Rahibiyah Che Wan Adnan (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2006